Impact of regular basic education on monetary poverty in the Huanuco region, Peru - Calero, Roberto (2023)
Objective. To determine the impact of having Regular Basic Education (EBR) studies on the  condition of being poor in the population of the Huánuco region (Peru), for the period 2010-2020. Methods. The research was applied, adopted an explanatory level and a non-experimental design. Human capital theory and data from the National Household Survey were used as a theoretical basis for the estimation of a probit model. Results. It was found that people with secondary education are less likely to be poor. In particular, it was found that the probability of being monetarily poor of a person with initial, primary and secondary education decreases by 0.11 pp, 2.19 pp and 3.60 pp, respectively. Conclusions. It is concluded that having a higher level of RBS education leads to a greater decrease in the probability of being poor from the monetary approach to poverty.